Traditional chinese medicine in Malaysia: A brief historical overview of education and research - Hon Foong Wong; Shih Chau Ng; Wen Tien Tan; Jun Liu; Xun Lin; Si Woei Goh; Bao Ling Hoo; Chyong En Chai; Huiying Wang (Wolters Kluwer Health/LWW, 2019)
The education and research of traditional Chinese medicine (TCM) in Malaysia started coincidentally circa Malaysia's independence movement. Before the independence, much of the development focused on establishing treatment centers and Chinese medical halls to provide TCM treatment. Periodicals and journals advocating TCM and its advancement were published between the 1940s and 1960s, but many did not survive after a few issues. The challenge posed by the Immigration Ordinance 1952 further united TCM practitioners and TCM associations to establish the Chinese Medical Institute of Malaya. The trend gained momentum, and many educational institutes were set up in each of Malaysia. From the 1970s, Malaysia started hosting regional and international TCM conferences. In 2000, TCM education in Malaysia had finally gained recognition from the government. A TCM program standard was thus released by the Malaysian Qualifications Agency (MQA). To date, there are seven private higher education institutions which offer TCM programs based on the MQA standards and have established international collaborations with other universities. It is projected that Malaysia's TCM education and research will grow further as a result of China's Belt and Road initiative.